giải phương trình: a,\(\sqrt[4]{5-x}+\sqrt[4]{x-1}=\sqrt{2}\) b,\(\sqrt[4]{x}+\sqrt[4]{17-x}=3\)
Giải phương trình: \(\sqrt{x^2+x+19}+\sqrt{7x^2-2x+4}+\sqrt{13x^2+19x+7}=\sqrt{3}.\left(x+5\right)\)
Giải phương trình:
\(11\sqrt{5-x}+8\sqrt{2x-1}=24+3\sqrt{\left(5-x\right)\left(2x-1\right)}\)
\(\sqrt{x+3}+2\sqrt{x}=2+\sqrt{x\left(x+3\right)}\)
giải bất phương trình \(\left(\sqrt{13}-\sqrt{2x^2-2x+5}-\sqrt{2x^2-4x+4}\right)\left(x^6-x^3+x^2-x+1\right)\ge0\)
Giải bất phương trình: \(\sqrt[4]{\left(x-2\right).\left(4-x\right)}+\sqrt[4]{x-2}+\sqrt[4]{4-x}+6x\sqrt{3x}\le x^3+30\)
Giải phương trình:
\(\sqrt{4-x^2}+6=2\sqrt{2+x}+3\sqrt{2-x}\\ \left(\sqrt{2-x}+1\right)^2=3x+1\)
Giải phương trình \(\dfrac{3\left(x-\sqrt{3}\right)\left(x-\sqrt{5}\right)}{\left(1-\sqrt{3}\right)\left(1-\sqrt{5}\right)}+\dfrac{4\left(x-1\right)\left(x-\sqrt{5}\right)}{\left(\sqrt{3}-1\right)\left(\sqrt{3}-\sqrt{5}\right)}+\dfrac{5\left(x-1\right)\left(x-\sqrt{3}\right)}{\left(\sqrt{5}-1\right)\left(\sqrt{5}-\sqrt{3}\right)}=3x-2\)
Giải phương trình:
\(\sqrt{x+2}+\sqrt{x-2}+2\sqrt{x^2-4}=2\left(3-x\right)\)
Giúp mk vs!!
giải hệ phương trình
\(\left\{{}\begin{matrix}\sqrt{x-2}+\sqrt{y-3}=3\\2\sqrt{x-2}-3\sqrt{y-3}=-4\end{matrix}\right.\)
\(\left\{{}\begin{matrix}\dfrac{3x}{x+1}+\dfrac{2}{y+4}=4\\\dfrac{2x}{x+1}-\dfrac{5}{y+4}=4\end{matrix}\right.\)